2011
DOI: 10.1534/genetics.110.125468
|View full text |Cite
|
Sign up to set email alerts
|

The Cik1/Kar3 Motor Complex Is Required for the Proper Kinetochore–Microtubule Interaction After Stressful DNA Replication

Abstract: In budding yeast Saccharomyces cerevisiae, kinetochores are attached by microtubules during most of the cell cycle, but the duplication of centromeric DNA disassembles kinetochores, which results in a brief dissociation of chromosomes from microtubules. Kinetochore assembly is delayed in the presence of hydroxyurea, a DNA synthesis inhibitor, presumably due to the longer time required for centromeric DNA duplication. Some kinetochore mutants are sensitive to stressful DNA replication as these kinetochore prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…61 In a genomewide screen for yeast deletion mutants that are sensitive to stressful DNA replication, both cik1Δ and kar3Δ mutants were isolated, presumably due to the defect in chromosome bipolar attachment. 62 Our further analysis indicates that the loss of function of Cik1/Kar3 increases the chance of syntelic attachment, although the mechanism for this incorrect attachment remains to be determined. Moreover, we found that overexpression of the coiled-coil domain of Cik1 (Cik1-CC) disrupts Cik1-Kar3 interaction, which allows us to conditionally inactivate the Cik1/ Kar3 motor complex and induce syntelic attachments.…”
Section: The Checkpoint Response To Tension Defects In Higher Eukaryomentioning
confidence: 76%
“…61 In a genomewide screen for yeast deletion mutants that are sensitive to stressful DNA replication, both cik1Δ and kar3Δ mutants were isolated, presumably due to the defect in chromosome bipolar attachment. 62 Our further analysis indicates that the loss of function of Cik1/Kar3 increases the chance of syntelic attachment, although the mechanism for this incorrect attachment remains to be determined. Moreover, we found that overexpression of the coiled-coil domain of Cik1 (Cik1-CC) disrupts Cik1-Kar3 interaction, which allows us to conditionally inactivate the Cik1/ Kar3 motor complex and induce syntelic attachments.…”
Section: The Checkpoint Response To Tension Defects In Higher Eukaryomentioning
confidence: 76%
“…Moreover, overexpression of the coiled-coil domain of CIK1 (CIK1-CC) disrupts Cik1-Kar3 interaction and induces an anaphase entry delay that depends on both Ipl1 and Sgo1 (9,18). Therefore, we also compared the Mad1 phosphorylation kinetics in wild-type (WT), ipl1, and sgo1 mutant cells overexpressing CIK1-CC.…”
Section: Resultsmentioning
confidence: 99%
“…To reestablish the KT-MT interaction, the disconnected kinetochores are first captured by a microtubule and then moved to the vicinity of one spindle pole through Cik1/Kar3-mediated transport (Tanaka et al. , 2005, 2007), which may facilitate chromosome bipolar attachment (Liu et al. , 2011).…”
Section: Resultsmentioning
confidence: 99%